“Be yourself, rediscover yourself, and find new aspects of yourself”: newcomer youth integration in a francophone school system - Molyneux, Tonje M.; Kassan, Anusha; Ty, Sophie V. (Frontiers in Education, 2024)
Negative school integration experiences can compromise the healthy development of newcomer youth. Little research has explored what affects their experiences; even less has engaged youth in the research process. This study investigated the school integration experiences of French-speaking newcomer youth in a predominantly anglophone Canadian province using the Arts-Based Engagement Ethnography research method. We explored: (1) How do newcomer youth experience a public francophone school? and (2) How do these experiences influence their positive integration into the francophone school system in a predominantly anglophone province? Data from artifacts, interviews, and planned group discussions were organized into four structures: (a) navigating school integration challenges, (b) negotiating identity, (c) confronting biases, and (d) helping other newcomer youth. Underlying patterns painted a rich portrait of newcomer youth school integration experiences, which informed their emerging identity. Findings point to needed changes to supports and services offered to newcomer youth integrating into the francophone school system in a predominantly anglophone province.